PENINGKATAN KOMPETENSI SISWA SMK MELALUI PELATIHAN SISTEM BAHAN BAKAR EFI - Wagino Wagino; Toto Sugiarto; M. Nasir; Ahmad Arif (PAKAR Pendidikan, 2018)
SMK students of Automotive department, Especially Light Vehicle Engineering, need some skills that will be used when students are finishing the study at school. One of the skill are they have good competency of electroni fuel injection system (EFI system). The purpose of the training program is to develop and improve the ability of automotive technology, especially ototronc technology, basic knowledge of EFI system, and to train and guide SMK student. For diagnostic and trouble shooting of EFI system. This training program uses the several method, i.e; presentation, watching video and animation of EFI system, discussion, demonstration, guidence and direct practical. After done this training, have improvement of knowledge and skill of trainee. On of indicator is improvement of postest value, i.e; have mean about 119% from pre-test value. Beside that, based on observation as long as training proggram, attitude and skills of trainees are better than befor.